Karakteristik Gel Sariawan Ekstrak Daun Sirih Hitam sebagai Antimikroba dengan Variasi Konsentrasi Carbopol - Karmila Puspita Sari; Jaka Fadraersada; Fajar Prasetya (Proceeding of Mulawarman Pharmaceuticals Conferences, 2020)
Betel plant is a terna plant that can be used as an antifungal, antimicrobial and antioxidant. Black betel leaf is proven to contain secondary metabolites of alkaloids, carotenoids, phenolic compounds, flavanoids, saponins, tannins, steroids, and triterpenoids. Gel preparations are used aimed at prolonging the contact time of the preparation with the target location, extending the absorption time and increasing the therapeutic effect. This study aims to determine the characteristics of gel extract of black betel leaf. Black betel leaf extract was obtained by macerating with 70% ethanol into an oral gel preparation as an antimicrobial with carbopol concentration variations. The results of antimicrobial test showed that 5% concentration of black betel leaf extract could increase the growth of Streptoccus sanguinis with inhibition zone diameter 6.261 ± 1.425mm and Candida albicans with inhibition zone diameter 5.152 ± 0.952mm. Black betel leaf extract gel formula F3 with 1.5% carbopol concentration is the best formula that has greenish black, betel and mint flavored, and has a thick and homogeneous shape. It has a viscosity of 2.266 Pa.s, has a pH of 5.37 and spread power 4.37cm.